If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -1(3 + -6x) * 2 = 0 Reorder the terms for easier multiplication: 2x + -1 * 2(3 + -6x) = 0 Multiply -1 * 2 2x + -2(3 + -6x) = 0 2x + (3 * -2 + -6x * -2) = 0 2x + (-6 + 12x) = 0 Reorder the terms: -6 + 2x + 12x = 0 Combine like terms: 2x + 12x = 14x -6 + 14x = 0 Solving -6 + 14x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 14x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 14x = 0 + 6 14x = 0 + 6 Combine like terms: 0 + 6 = 6 14x = 6 Divide each side by '14'. x = 0.4285714286 Simplifying x = 0.4285714286
| e^4x+3e^2x-10=0 | | 5B+4B=90 | | 5x-2(x-5)=-8+5x+6 | | 4x+132=7x+257 | | -1/7(7-14x)=11 | | M+m+2m-3m=11 | | 4p-p+4p-5p-p=17 | | (5x-1)(6x+8)=0 | | 152+15m=407 | | 32n-171=437 | | 9u-8u=16 | | 7(6+8)=t-4+2 | | .25z=2.75 | | 2t^2+t+10=6 | | 7v-4v=9 | | 4x+52=202 | | 16j+4j=20 | | 4.78+z=15.78 | | 6.5z=71.5 | | 12r-8r=16 | | 3(x+2)-2x=2(x+5) | | 4x+52+2x=202 | | 4x+52+1x=202 | | 6x+5+3x=25 | | 6t+1=7t | | 2a-7=3a | | 10x-I=2a-(-5) | | 136+7m=269 | | 26n-187=255 | | 3x^2-25x-19=0 | | 11.11n+9=-4n | | ln(x+2.5)=12-ln(x+1.3) |